The Influence of Transformational Leadership, Academic Culture, and Knowledge Sharing on Lecturers' Performance at Universities - Supriatna, Supriatna (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This study aims to examine the partial and simultaneous effects of transformational leadership, academic culture, and knowledge sharing on lecturers' performance at Al-Ihya Kuningan Islamic University. Lecturers' performance is a crucial indicator of higher education quality as it is directly related to the implementation of the tridharma of higher education, namely teaching, research, and community service. This research employed a quantitative approach using a descriptive-verificative method. The data in this study consisted of primary data obtained from lecturers through questionnaire responses and secondary data derived from institutional documents, performance reports, and relevant higher education records. Data were collected through a Likert-scale questionnaire distributed to lecturers as research respondents. The collected data were analyzed using simple linear regression and multiple linear regression with the assistance of SPSS software. The results indicate that transformational leadership, academic culture, knowledge sharing, and lecturers' performance were categorized as moderately good, with average scores of 68.4%, 70.1%, 72.6%, and 69.8%, respectively. Partial regression analysis shows that transformational leadership (Sig. = 0.024), academic culture (Sig. = 0.017), and knowledge sharing (Sig. = 0.000) have a positive and significant effect on lecturers' performance. Furthermore, multiple regression analysis confirms that these variables simultaneously have a significant effect on lecturers' performance (Sig. = 0.000), with knowledge sharing as the most dominant variable. This study concludes that improving lecturers' performance requires the synergy of inspirational transformational leadership, a supportive academic culture, and a structured and sustainable knowledge-sharing system within higher education institutions.